Analysis of the Application of Fixed Assets Accounting in the Preparation of the Balance Sheet at the North Sulawesi Provincial Office of Cooperatives and SMES - Frizki Rahmayanti Irooth; Inggriani Elim; Natalia Y. T. Gerungai (Formosa Journal of Multidisciplinary Research, 2023)
The more rapid development of technology at this time the community has also thought rationally that the importance of entrepreneurship. To support each activity, the cooperative service will utilize the assets owned. Fixed assets also have an important role, therefore the accounting treatment in the recognition and measurement of fixed assets must be in accordance with Government Accounting Standards. The cooperative service is engaged in controlling public services and receiving results from every cooperative and micro business in North Sulawesi. Therefore the cooperative service has a variety of fixed assets with a fairly high value. In the government's financial statements, fixed assets also play a role in the government's budget, so the recognition, measurement, valuation and disclosure of fixed asset information is very important in the financial statements of an entity. The purpose of this study is to determine the suitability of Accrual-Based Government Accounting Standards Application in Permendagri No. 64 of 2013 concerning Fixed Assets in the Preparation of Balance Sheets at the North Sulawesi Provincial Office of Cooperatives and SMEs in accordance with Statement of Government Accounting Standards No. 07 Concerning Fixed Assets by conducting research that is descriptive qualitative in nature. The results of the study show that the application of accrual-based government accounting standards in Permendagri no. 64 of 2013 concerning fixed assets in the preparation of the balance sheet is in accordance with the government accounting standard statement 07 regarding fixed assets and the Cooperative Office does not apply depreciation of fixed assets so that when the economic useful life has expired the Cooperative Office will write off goods.